A comparative evaluation of the fluoride content in commercially available infant formulae in India: An in vitro study - Asha Supriya Satti; Radhika Muppa; Ravichandra Sekhar Kotha; Srikanth Koya; Mrudhula J N. Kantipudi; Deepthi Siva Harika Ch (Wolters Kluwer Medknow Publications, 2023)
Context: The most critical period for enamel fluorosis to develop is during the early years of life when enamel formation occurs. To minimize the risk of dental fluorosis development, monitoring fluoride intake during teeth development has been suggested. As infant formulae are major source of nutrition in infants, it is important to determine the fluoride content in them in order to monitor the fluoride intake in infants. Aims: To estimate and comparatively evaluate the fluoride content in different commercially available infant formulae in India. Methodology: A total of 16 commercially available infant formulae were collected from local pharma/grocery stores, in which 14 were milk based (Group M) and 2 were soy based (Group S). Fluoride content of the formulae was evaluated using ORION F selective electrode. Statistical Analysis Used: ANOVA test, t-test. Results: The mean F values for groups M and S were found to be 0.031 and 0.07 ppm, respectively. Fluoride content of milk-based formulae was significantly lesser (P < 0.001) than soy-based formulae. Daily fluoride intake through the tested formulae was in the range of 0.013 mg and 0.105 mg when calculated following the manufacturer's preparation guidelines. Conclusions: Infant formulae alone were unlikely to be a risk factor for dental fluorosis, but when reconstituted with optimally fluoridated water, they can be a risk factor for the development of dental fluorosis.